Kitab Al- ru’ya (The book of dream) in Sahih Muslim - López Brenes, Manuel Enrique (2017)
The Sahih Muslim was compiled by Muslim and it contains a great amount of ahadith (sayings and deeds of Prophet Muhammad, the Rasul Allah). This compilation of ahadith contains various themes. One of them is concerning dreams, which Muslim compiled in a book entitled Kitab al Ru’ya, The Book of Dreams. In Islam dreams can be good and they are known as Ru’ya. These are the ones inspired by Allah. Bad dreams are known as Hulm and they are inspired by Shaytan (Satan). If someone has a bad dream (hulm) he has to spit three times from his left side and seek refuge in Allah. This way Shaytan cannot harm him. In Muslim tradition dreams are of an extraordinary importance and the interpretation or interpretations are also relevant. Very frequently interpreters of dreams give a clear religious meaning or interpretation to the dreams, as this issue is analysed in this essay. In this paper dreams are studied under the Muslim tradition, as well as Prophet Muhammad’s dreams, as all of this is contained in the Sahih Muslim.